KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA TOKO TRADISIONAL DAN TOKO MODERN DI SANGATTA - Nuradillah, Nuradillah Nuradillah (EKONOMIA, 2016)
Customer Satisfaction Shops Traditional and Modern Stores Sangatta. Model analysis used to determine the effect of Quality of Service to Customer Satisfaction is a Comparative Analysis of Two samples were correlated.The results of the analysis and discussion shows that the variable quality of services consisting of physical evidence, reliability, responsiveness, assurance and attention together (simultaneously) significantly affects customer satisfaction Shops Traditional and Modern Stores Sangatta, with a count of 0,313 with the numbers no significance amounting to 0.313 <0.05, and sig. (2-tailed) was not of significance of 0.207 <0.05. Where the physical evidence did not significantly affect customer satisfaction with the significant value of 0.002> 0.05. And sig. (2-tailed) was not of significance of 0.036 <0.05. Reliability no significant effect on customer satisfaction with the value of no significance 0.092 <0.05. And sig. (2-tailed) significance of 0.000> 0.05. Responsiveness not significant effect on customer satisfaction with the value of no significance at 0.487> 0.05. And sig. (2-tailed) significance of 0.04> 0.05. Signifikan.Kepuasan influential assurance customers with no significance value of 0.327 <0.05. And sig. (2-tailed) was not of significance of 0.001> 0.05